Wireless Virtual Multiple Antenna Networks for Critical Process Control: Protocol Design and Experiments. (23rd April 2013) - Savazzi, Stefano
Abstract : Wireless telemetry systems for remote monitoring and control of industrial processes are now becoming a relevant topic in the field of networked control. Wireless closed-loop control systems have stricter delay and link reliability requirements compared to conventional sensor networks for open-loop monitoring and call for the development of advanced network architectures. By following the guidelines introduced by recent standardization, this paper focuses on the most recent technological advances to enable wireless networked control for tight closed-loop applications with cycle times below 100 ms. The cooperative network paradigm is indicated as the key technology to enable cable replacing even in critical control applications. A cooperative communication system enables wireless devices placed at geographically separated locations to act as a virtual ensemble of antennas that creates a virtual multiple-antenna-distributed system. A proprietary link-layer protocol/based on the IEEE 802.15.4 physical layer has been developed and tested in an indoor environment characterized by non-line-of-sight (NLOS) propagation and dense obstacles. The measurements obtained from the testbed evaluate experimentally the benefits (and the limitations) of cable replacing in critical process control.